PENGARUH SUHU AIR TERHADAP DAYA TETAS TELUR DAN PERKEMBANGAN LARVA NILA MERAH (Oreochromis sp.) - Rustadi Rustadi (Universitas Gadjah Mada, 2002)
Artificial incubations of red tilapia eggs and fry were conducted in the effort to increase fish seed production and its quality. These experiments were done to determine suitable water temperature for egg incubation and larvae rearing. Four different water temperatures, 24, 27, 30, and 33oC with variance 1oC and ambient temperature were tested in triplicates. One liter of plastic incubators made from soft drink bottles were set to water re-circulation system and provided with filter means.The fertilized eggs were stocked at 150 eggs. The hatching rate of egg increased as the increase of water temperature. The increase of water temperature decreased the incubation time of eggs, but increased hatching rate and the growth of larvae. The optimum water temperature was 29,87oC.